Psychological Guidance for Independent Adolescents Program in PSAA Ceger and Tebet Jakarta - Penny Handayani; Novita W. Sutantoputri; Anissa Azura (Institute for Research and Community Services, 2019)
Ceger and Tebet Childcare Social Institution (PSAA) is the Technical Service Unit of the DKI Jakarta Provincial Social Service that provides services for adolescents at junior and senior high school levels. As a social care institution, it is undeniable that fulfilling psychological needs is just as important as fulfilling physical needs. Various problems that arise in foster children are usually concerned with lack of fulfillment of psychological needs. When an individual reaches the adolescent phase, the need for psychological fulfillment changes. In the adolescent phase, independence is one of the main development tasks that need to be mastered, so the focus of assistance in 2018 was directed to preparation for orphanage youths in facing life after the orphanage, which will begin after they graduate from high school. The present community service activity aims to provide psychological assistance for children of PSAA Putra Utama 3 Tebet and Putra Utama 4 Ceger Jakarta to help them become independent and to be ready to face life after high school, with an understanding of how to effectively manage themselves and manage others in personal and professional situations. Through this program, participants were expected to be able to learn the following skills: be independent and ready to work, manage themselves, and manage others. The community mentoring training module was designed based on the typical characteristics of participants fromm PSAA Putra Utama 3 Tebet and 4 Ceger during the 11 month assistance period. It can also be used by the PSAA to run training-based mentoring intervention programs independently in the future.